3D printing : fundamentals to emerging applications / edited by Ram K. Gupta. - Gupta, Ram K. (CRC Press, 2023)
This comprehensive work provides the fundamentals of 3D printing technologies, current state-of-the-art knowledge, and their emerging applications. This is a suitable textbook for students and a must-have resource for researchers and industry professionals working in energy, biomedical, materials, and nanotechnology fields.